2019
DOI: 10.21608/jappmu.2019.48272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hen Oviposition Time on some Egg Characteristics

Abstract: Ovulation in chicken is the process of emergence the egg yolk by controlling the steroid hormones, which is followed by oviposition that influence by several factors. Egg yolk is a huge oocyte contains fat in water emulsion with about 50% dry weight, its rounded and centrally located. The experiment was carried out to investigate the effect of oviposition time on egg external traits (egg weight, egg length, egg breadth), yolk characteristics (yolk weight, yolk high, yolk diameter, yolk index, and the proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The egg-shape index in the presented study was, on average, 79.78%. Shaker et al (2019) showed an egg-shape index of 76.29 to 79.32%. Eggs were obtained from hens at the age of 30 wk.…”
Section: Discussionmentioning
confidence: 99%
“…The egg-shape index in the presented study was, on average, 79.78%. Shaker et al (2019) showed an egg-shape index of 76.29 to 79.32%. Eggs were obtained from hens at the age of 30 wk.…”
Section: Discussionmentioning
confidence: 99%
“…In Japanese quail the egg weight was higher in the grey feather color line, intermediate in the brown feather color, and low in the white feather color [7]. Moreover the external egg traits were correlated significantly with age [8], Oviposition [9], genotype [10], species [11], environment [12], and the flock health. By using PCA, [1] was could to set the component affect the egg weight.…”
Section: Introductionmentioning
confidence: 99%
“…External egg traits (Length, and breadth) play important roles for embryo growing [2], and chick survival. It's high correlated with species [3][4][5], genotype [6][7][8][9][10], age [7][8][9][10][11], oviposition time [12], and hen health. Also it defer between the birds in same species [13].…”
Section: Introductionmentioning
confidence: 99%